Avaliação in vitro da citotoxicidade celular do cimento de ionômero de vidro modificado por carbonato de cálcio de conchas marinhas - Giacomelli, édio (2012)
This study aimed to evaluate the cytotoxicity and bioactivity of the glass ionomer cement modified with calcium carbonate shells. For testing cell toxicity was using Saccharomyces cerevisiae as a model organism. The induction of cytotoxicity was evaluated by two different tests using wild-type strain FF18733 of S. cerevisiae: (1) yeast cell survival and (2) formation of petite colonies (respiratory mutants). For tests of bioactivity was evaluated weight change of samples and analysis of hydroxyapatite deposition by SEM and EDS after immersion in simulated blood plasma. The results of survival tests showed that different concentrations of calcium carbonate added to the GIC (1%, 5% and 10% by weight) induced a slight loss of cell viability in S. cerevisiae in relation to the negative control, but it was not enough to be considered as a significant induction of toxicity. In relation to the petite colonies, there was no induction of mutants respiratory formation in any of the concentrations tested, indicating that the GIC did not induce altered oxidative stress in cells of S. cerevisiae. In the evaluation of bioactivity, the results showed that after immersion all groups tested showed a decrease in weight of the samples, which can be attributed to the dissolution of glass ionomer cement. In the fourth week of immersion there was a significant variation in the average percentage of weight for all groups. The SEM analysis showed a slight deposition of hydroxyapatite on the surface of the groups with the addition of powdered shells compared to the control group.